Influence of deformation temperature on structural variation and shape-memory effect of a thermoplastic semi-crystalline multiblock copolymer - W. Yan; L. Fang; U. Noechel; K. Kratz; A. Lendlein (eXPRESS Polymer Letters, 2015)
A multiblock copolymer termed as PCL-PIBMD, consisting of crystallizable poly(ε-caprolactone) (PCL) segments and crystallizable poly(3S-isobutyl-morpholine-2,5-dione) (PIBMD) segments, has been reported as a material showing a thermally-induced shape-memory effect. While PIBMD crystalline domains act as netpoints to determine the permanent shape, both PCL crystalline domains and PIBMD amorphous domains, which have similar transition temperatures (Ttrans) can act as switching domains. In this work, the influence of the deformation temperature (Tdeform = 50 or 20°C), which was above or below Ttrans, on the structural changes of PCL-PIBMD during uniaxial deformation and the shapememory properties were investigated. Furthermore, the relative contribution of crystalline PCL and PIBMD amorphous phases to the fixation of the temporary shape were distinguished by a toluene vapor treatment approach. The results indicated that at 50°C, both PCL and PIBMD amorphous phases can be orientated during deformation, resulting in thermallyinduced crystals of PCL domains and joint contribution to the switching domains. In contrast at 20°C, the temporary shape was mainly fixed by PCL crystals generated via strain-induced crystallization.